(untitled) (Bangladesh Journal of Medical Science, 2021)
Introduction: The frequency of births of infants with perinatal pathology has increased inrecent years. The aim of this study is to determination of lead content in the biomedias ofnewborns with hypoxic-ischemic damage of the central nervous system (CNS). Materials andMethods: We studied influence of the lead content in children, which were born with hypoxicischemiclesion CNS (HIL CNS). Determination of this microelement was carried out in theblood serum, erythrocytes and urine of 30 newborn infants which were suffered from asphyxiaafter birth. The comparison group consisted of 30 healthy full-term newborns. Results: In thebiomedias of children with the HIL of the central nervous system, a toxic trace element of leadhas been identified which is poorly retained in the placenta, so the fetus is more vulnerable toits toxic effects in the prenatal period. In the article the features of the lead content in serum,erythrocytes and urine in term infants which were born with hypoxic-ischemic CNS lesions areinvestigated. This group of subjects had increased serum and erythrocyte concentration of lead.The high content of lead in the erythrocytes of children with hypoxia which is already at birthmay indicate a transplacental penetration of this toxic trace element and the possibility of itsnegative impact on the course of pregnancy. Conclusions: The prognostic significance of thelead content was high. Thus, the informative index (Ī) for lead content in serum is 7.40, and theprognostic factor (PC) is + 15.1. As for the prognostic value of the lead content in erythrocytesand urine, very high predictor properties are established for them: Ī = 7.44; PC = + 7.0 and Ī =13.42; PC = + 16.1 respectively. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.330-333